2006
DOI: 10.1007/s11010-005-9047-9
|View full text |Cite
|
Sign up to set email alerts
|

Urinary liver-type fatty acid binding protein as a useful biomarker in chronic kidney disease

Abstract: Urinary excretion of L-FABP increases with the deterioration of renal function. Serum L-FABP did not influence on urinary L-FABP. Urinary L-FABP may be a useful clinical biomarker for monitoring CKD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
105
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 154 publications
(115 citation statements)
references
References 7 publications
8
105
0
2
Order By: Relevance
“…Kamijo et al demonstrated that in patients with mild nondiabetic CKD, significantly higher L-FABP levels were associated with a more rapid rate of CKD progression. Notably, neither serum creatinine nor urine protein differed between patients who did versus those who did not experience rapid CKD progression (26), similar to our study findings. The elevated urinary IL-18 and L-FABP levels in the AKI-positive patients in our cohort could support ongoing inflammation as a source of kidney injury.…”
Section: Discussionsupporting
confidence: 91%
“…Kamijo et al demonstrated that in patients with mild nondiabetic CKD, significantly higher L-FABP levels were associated with a more rapid rate of CKD progression. Notably, neither serum creatinine nor urine protein differed between patients who did versus those who did not experience rapid CKD progression (26), similar to our study findings. The elevated urinary IL-18 and L-FABP levels in the AKI-positive patients in our cohort could support ongoing inflammation as a source of kidney injury.…”
Section: Discussionsupporting
confidence: 91%
“…The utility of urinary L-FABP in various chronic kidney disease (CKDs) has been reported. 31 A number of studies have suggested a possible role for urinary FABP in clinical diagnosis of renal disease. 32 Ferguson et al have reported a substantial increment of urinary L-FABP in several etiologies of acute kidney injury (AKI) such as acute tubular necrosis, nephrotoxic exposure, and sepsis.…”
mentioning
confidence: 99%
“…10 Therefore, a biomarker that demonstrates the kidney injury in an earlier stage has been sought, and NGAL, NAG, and L-FABP have been demonstrated to reflect the renal damage in the early period. [19][20][21][22][23][24][25][26][27][28][29] NGAL, one of the members of lipocalin family with a 25 kDa molecular weight, is a protein in the small glycoprotein structure. It is released from renal tubular cells, hepatocytes, and endothelial cells as a response to cellular stress in certain conditions, such as ischemia and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 Its excretion from the proximal tubule increases in tubulointerstitial damage. 28 The amount of urinary L-FABP has been found to increase in a short time after AKI in some conditions, such as acute tubular necrosis, sepsis, and cardiac surgery. 8,9,26,29 In a study in Japan, L-FABP levels were found to be positively correlated with the severity of renal ischemia.…”
Section: Discussionmentioning
confidence: 99%